2010
DOI: 10.1524/ract.2010.1719
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium release from fuel in accident conditions

Abstract: During a hypothetical nuclear power plant accident, fission products may be released from the fuel matrix and then reach the containment building and the environment. Ruthenium is a very hazardous fission product that can be highly and rapidly released in some accident scenarios. The impact of the atmosphere redox properties, temperature, and fuel burn-up on the ruthenium release is discussed. In order to improve the evaluation of the radiological impact by accident codes, a model of the ruthenium release from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Ruthenium is usually considered as a low volatile fission product, with less than 5% releases, but in some conditions involving ruthenium oxides formation, as shown during the VERCORS HT2 tests dealing with the fission product release from UO 2 fuel with a moderate burn-up [48 (GWd/tU)], in pure steam, the ruthenium released amounted to 60% of the fuel inventory and a relevant part (12%) was transported as the oxide form and not deposited in the experimental line, even at quite a low temperature (150 °C). Some modelings were performed , to predict ruthenium release from the fuel. Concerning ruthenium transport in the reactor coolant system, recent experimental works ,,, were devoted to better characterize deposits and gas phase of ruthenium oxides along a thermal gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruthenium is usually considered as a low volatile fission product, with less than 5% releases, but in some conditions involving ruthenium oxides formation, as shown during the VERCORS HT2 tests dealing with the fission product release from UO 2 fuel with a moderate burn-up [48 (GWd/tU)], in pure steam, the ruthenium released amounted to 60% of the fuel inventory and a relevant part (12%) was transported as the oxide form and not deposited in the experimental line, even at quite a low temperature (150 °C). Some modelings were performed , to predict ruthenium release from the fuel. Concerning ruthenium transport in the reactor coolant system, recent experimental works ,,, were devoted to better characterize deposits and gas phase of ruthenium oxides along a thermal gradient.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that additional data are required in order to make a reliable assessment of the ruthenium outside releases in case of severe accident. Since this literature survey in 1986, many works were performed on this topic to fill the gap in the prediction of ruthenium behavior. Ruthenium is usually considered as a low volatile fission product, with less than 5% releases, but in some conditions involving ruthenium oxides formation, as shown during the VERCORS HT2 tests dealing with the fission product release from UO 2 fuel with a moderate burn-up [48 (GWd/tU)], in pure steam, the ruthenium released amounted to 60% of the fuel inventory and a relevant part (12%) was transported as the oxide form and not deposited in the experimental line, even at quite a low temperature (150 °C).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences in case of accident can be estimated using FP release models that take into account FP localization and speciation in fuel pellets. FP can be classified among groups depending on their degree of volatility: volatile like Xe, Kr, Cs, I and Te, semi-volatile like Ba, Mo, Sr and Ru, low-volatile like Zr and Ce and non-volatile [1,2]. FP of the first group are highly and rapidly released and the release is governed by atomic diffusion within fuel grains.…”
Section: Introductionmentioning
confidence: 99%
“…The filter paper collection was part of a larger event where 106 Ru was detected across Europe during several months in the fall of 2017. , The stable Ru isotopic composition in the paper was consistent with release from spent fuel and comparison with select values reported for different reactor types pointed toward a water–water energetic reactor (VVER) as the source of the emissions . This prior work suggested that 106 Ru measurements could have important future applications in environmental monitoring, as this volatile radioisotope (RuO 4 , boiling point: 40 °C) can be released in nuclear accidents and other nuclear activities. , …”
Section: Introductionmentioning
confidence: 91%